Project Based Flipped Learning (PjBFL) Model in Increasing Effectiveness Learning : A Systematic Literature Review - Suciati, Ni Nyoman Ayu; Agustini, Ketut; Dantes, Gede Rasben; Sudhata, I Gde Wawan (Jurnal Paedagogy, 2025)
This study aims to examine the effectiveness of the implementation of PjBFL in improving 21st-century skills and identify interactive media that support its implementation through the Systematic Literature Review (SLR) method. The literature analyzed came from accredited journals indexed in the Scopus and Google Scholar databases, with a publication range of 2020–2024. The search keywords included "Project-Based Flipped Learning", "PjBFL", "flipped classroom", and "project-based learning". All articles found were selected using inclusion and exclusion criteria based on topic focus and full-text availability. The data selection and analysis process was carried out based on the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) which includes the stages of identification, screening, feasibility assessment, and reporting. The results of the analysis of 20 journals showed that PjBFL is effective in improving critical thinking skills, collaboration, creativity, problem solving, and learning motivation, especially at the higher education level. The interactive media that are predominantly used include Learning Management Systems (LMS), learning videos, e-modules, and digital communication applications. However, challenges such as low student engagement, student digital literacy and teacher readiness in producing digital content are still obstacles to implementation. Therefore, it is necessary to train educators, provide adequate digital infrastructure, and adapt content that is appropriate to the level of education and learning styles of students. This finding underlines the great potential of PjBFL in improving the effectiveness of learning in the digital era.